Heterotaxy syndrome with accompanying azygos continuation of the inferior vena cava, patent ductus arteriosus and replaced common hepatic artery - Güngör, Candan; Akay, Emrah; Yılmaz, Sena; Yanık, Bahar (Journal of Surgery and Medicine, 2021)
Abnormal anatomical organization of thoraco-abdominal visceral organs and vascular structures is called “Heterotaxy Syndrome.” Heterotaxy is generally classified under two main headings as polysplenia and asplenia syndromes. Complex cardiac anomalies are closely associated with poor prognosis in the patient group with asplenia syndrome. On the other hand, cardiac anomalies are less common in polysplenic syndrome. It is particularly important to define the findings accurately in the planning of surgical and interventional treatment. We present the findings of a patent ductus arteriosus (PDA) patient with co-existent heterotaxy syndrome associated with abdominal anomalies, such as polysplenia, azygos continuation of interrupted inferior vena cava, liver with midline localization, short pancreas, preduodenal portal vein, replaced common hepatic artery (HA) originating from the superior mesenteric artery (SMA) and left sided superior mesenteric vein to the SMA. To the best of our knowledge, there is no previous report of HA originating from the SMA found together with PDA and heterotaxy syndrome.